THE LEADERSHIP STYLE IN DECISION MAKERS BY HEAD OF SUB-DISCTRICT AS AN EFFORT TO INCREASE PUBLIC PARTICIPATION IN DEVELOPMENT (STUDY IN JEMBER LOR VILLAGE, PATRANG DISTRICT, JEMBER REGENCY) - Kristanto, Roedie Harie (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study discusses the leadership style of the village head in decision-making as an effort to increase community participation in development in Jember Lor Village, Patrang District, Jember Regency. Method: Using a qualitative descriptive method, this study collected data through in-depth interviews, direct observation, and documentation. Results: The results show that the village head applies a democratic leadership style that allows the community to actively participate in development planning and implementation. Community participation has increased significantly in deliberations, development activities, and program proposal submissions. Greater community involvement has a positive impact on the effectiveness and quality of development programs. However, there are still challenges in increasing participation, especially from underrepresented community groups. Novelty: This study highlights the need for a more inclusive approach to ensure that the entire community can play an active role. The findings provide insight for regional leaders in implementing a more participatory and effective leadership style in community development.